Tailoring the hydrophobicity of copper surface with ion beam irradiation. Issue 3 (3rd April 2019) - Baghel, Vishakha; Sharma, Deepak Kumar; Sikarwar, Basant Singh; Kumar, Ranjit; Avasthi, D. K.
ABSTRACT: Dropwise condensation of water vapor present in moist air on copper surface is of significant scientific interest worldwide, for developing an efficient condensing unit of water harvesting via dewing devices. However, it does not prolong for a long duration on these surfaces because of the highly reactive nature of copper. In this work, simple and economically viable methods are described for altering the morphology of copper surfaces which exhibit dropwise condensation for long duration. The durable hydrophobic copper surfaces are fabricated by electrochemical deposition and solution immersion methods on chemically etched copper samples, followed by ion beam irradiation of 15 keV Ne ions at a fluence of 10 17 ions/cm 2 . The roughness of tailored samples is measured using atomic force microscope and contact angle measurements are performed for measuring the static contact angle of deionized water droplets on these modified surfaces. The results show that the irradiated surfaces have low contact angle hysteresis and prolonged dropwise condensation of water vapor present in moist air.